2020
DOI: 10.3390/w12030903
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cyanotoxin-Producing Genes in a Eutrophic Reservoir (Billings Reservoir, São Paulo, Brazil)

Abstract: CyanoHABs (cyanobacterial harmful algal blooms) are blooms of cyanobacteria capable of producing cyanotoxins, a large group of secondary metabolites that are toxic to most eukaryotes. In this work, the main aim was to evaluate the presence of multiple genes from each of the clusters responsible for biosynthesis of cyanotoxins (cylindrospermopsin, microcystin and saxitoxin) in total DNA obtained from sixteen environmental water samples by PCR. Microcystin gene mcyE was amplified in all analyzed samples. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
3
9
0
Order By: Relevance
“…These ndings of PCR ampli cation were same for both the years of study. Previous studies have also shown the identi cation and detection of toxic cyanobacteria in environmental samples based on mcy genes using a PCR technique (Baker et al 2002, Ribeiro et al 2020) with universal primers targeting conserved sequences (Hisbergues et al 2003) and species-speci c primers designed based on differences within the mcy gene clusters (Rantala et al 2006), respectively. The mcy genes preferably targeted are mcyA, B, C, D and E however, in several studies a combination of the mcy genes were used (Ouellette et al 2006).…”
Section: Spatial-temporal and Water Quality Index (Wqi) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These ndings of PCR ampli cation were same for both the years of study. Previous studies have also shown the identi cation and detection of toxic cyanobacteria in environmental samples based on mcy genes using a PCR technique (Baker et al 2002, Ribeiro et al 2020) with universal primers targeting conserved sequences (Hisbergues et al 2003) and species-speci c primers designed based on differences within the mcy gene clusters (Rantala et al 2006), respectively. The mcy genes preferably targeted are mcyA, B, C, D and E however, in several studies a combination of the mcy genes were used (Ouellette et al 2006).…”
Section: Spatial-temporal and Water Quality Index (Wqi) Analysismentioning
confidence: 99%
“…Number of analytical techniques such as protein phosphatase inhibition assay (PPIA), enzyme-linked immunosorbent assay (ELISA), highperformance liquid chromatography (HPLC), mass spectrometry (MS) has been employed for the monitoring of different MCs in the contaminated water samples (Kumar et al 2020a; Massey et al 2020). Molecular technique such as polymerase chain reaction (PCR) based detection of mcy genes (mcyA, mcyB, mcyD, mcyE and mcyG) is rapid, cost-effective as well as facilitated the culture independent identi cation of toxic cyanobacteria in environmental samples (Genuario et al 2010; Ribeiro et al 2020). Numbers of studies were available on the assessment of river Ganga water quality based on physico-chemical parameters, bacterial and fungal diversity and metal toxicity (Behera et al 2020;Matta et al 2020;Prasad et al 2020;Dimri et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The identification and quantification of cyanobacteria by traditional microscopy is not adequate for the identification of toxic populations, since toxic and nontoxic strains are morphologically identical [11]. For the detection of toxin-producing strains, PCR-targeting genes that encode specific toxins may be a fast and useful approach [12]. If the number of potentially toxin-producing cyanobacteria is needed, e.g., in environmental studies, quantitative PCR (qPCR) can be applied and serve as a powerful and sensitive tool [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, relatively few studies have focused on molecular approaches for the detection of toxic genes for early warning of cyanotoxin episodes, despite the frequent occurrence of cyanobacterial blooms [12,[18][19][20][21]. In most cases, traditional PCR was used to detect the presence of potentially cyanotoxin-producing strains, but the application of qPCR-targeting genes in the MC synthesis was performed by Lorenzi [19], Pimentel and Giani [11] and Guedes et al [22] to quantify the mcyA gene in Salto Grande reservoir, the mcyD gene in Furnas reservoir and the mcyB in Funil reservoir, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several freshwater ecosystems in tropical regions are subjected to anthropic disruptions, which promote the degradation of the water quality and the ecological patterns of resident species (Heath, 1990;Ogashawara et al, 2014;Ribeiro et al, 2020). The Billings Reservoir is in the Upper Tietê River Basin, on the Billings-Tamanduateí sub-basin and is the main reservoir for water supply in the Metropolitan Region of São Paulo (MRSP) (approximately 15% of the MRSP population) (SIGRH, 2009;Risso et al, 2018).…”
Section: Introductionmentioning
confidence: 99%